2019
DOI: 10.1042/bsr20182057
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of high expression of stanniocalcin-2 in hepatocellular carcinoma

Abstract: To investigate the significance of stanniocalcin-2 (STC2) expression in hepatocellular carcinoma (HCC) tissues and adjacent tissues. Levels of STC2 in HCC tissue were detected in 200 HCC patients tissues and adjacent tissues as controls by immunohistochemistry technique (IHC) and reverse transcriptase-PCR (RT-PCR). Single factor analysis was used to study the relationship between expression of STC2 mRNA and protein and clinicopathological features of HCC. Multifactor Cox survival analysis was used to relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Both STC2 mRNA and protein expression were related to tumor size, stage, metastasis, and differentiation in hepatocellular carcinoma. The hepatocellular carcinoma patients with higher expression of STC2 also had shorter median survival time (68). Furthermore, ectopic expression of STC2 promoted hepatocellular carcinoma cell proliferation and colony formation.…”
Section: Tumor Biologymentioning
confidence: 89%
See 2 more Smart Citations
“…Both STC2 mRNA and protein expression were related to tumor size, stage, metastasis, and differentiation in hepatocellular carcinoma. The hepatocellular carcinoma patients with higher expression of STC2 also had shorter median survival time (68). Furthermore, ectopic expression of STC2 promoted hepatocellular carcinoma cell proliferation and colony formation.…”
Section: Tumor Biologymentioning
confidence: 89%
“…Role of STC2 in human cancers has been studied from two different perspectives namely expression of STC2 in specific cancer models and cell lines, and STC2's function in cell growth, differentiation and apoptosis. Several reports suggest elevated expression of STC2 in human hepatocellular carcinoma, neuroblastoma, breast cancer, colorectal cancer, renal cell carcinoma, esophageal squamous cell cancer, and prostate cancer (41,(64)(65)(66)(67)(68)(69). Additionally, expression of STC2 was correlated with tumor invasion, metastasis and size in gastric cancers and hepatocellular carcinoma (70).…”
Section: Tumor Biologymentioning
confidence: 98%
See 1 more Smart Citation
“…Umezaki et al concluded that LOX induced epithelial-mesenchymal transition and could be used to predict intrahepatic metastasis in HCC ( 35 ). Wang et al ( 36 ) reported that high expression of STC2 may be associated with HCC occurrence, development, and prognosis. Although no evidence has been found to support the three other genes, they may be novel predictors in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…STC2 is involved in the paracrine and autocrine regulation by expressing in tissues and participating in phosphateregulating physiology, metabolism, regeneration, stress response and development [21,22] . Moreover, it was discovered that expression of STC2 changed overtly in solid cancers such as colorectal cancer, nasopharyngeal carcinoma, endometrial carcinoma, gastric carcinoma, hepatocellular carcinoma, SCCHN, which indicated that STC2 took effect in cancer development and progression, including promoting cancer cells invasion and metastasis, suppressing the cells apoptosis and so on [23][24][25][26][27][28] . Our finding of confirmatory test also demonstrated that STC2 may take part in regulatory network of…”
Section: Evaluation Of Cancer-promoting Mechanism Of Lncrna Mafg-as1mentioning
confidence: 99%